Influência da concentração de antioxidante na estabilidade do ácido retinóico - Rangel, Vera Lucia Borges Isaac [UNESP]; De Carvalho, Dermeval (My University, 2002)
Retinoic acid, which has been prescribed for some forms of acne since 1962, is subject to isomerization provoked by atmospheric oxygen and ambient light. Therefore it is very important to keep this material intact through the use of antioxidants. We tested two antioxidants: various concentrations of butylhydroxytoluene or BHT, widely used in cosmetic and dermatological preparations, and vitamin E, found in grape oil, an ingredient of skin lotion. Recently prepared lotions were subject to heat stress and the residual concentrations of retinoic acid determined at predetermined intervals through UV spectrophotometry. The shelf life of the various preparations were determined by the Arrhenius equation. The antioxidants helped conserve the retinoic acid, however, there was no synergism in antioxidant activity between the vitamin E in the grape seed oil and BHT.
Influence of the concentration of the antioxidant in the stability of retinoic acid
Keywords: Acne; Antioxidant; Butylhydroxytoluene; Retinoic acid; Vitamin E; alpha tocopherol; antioxidant; butylcresol; cosmetic; retinoic acid; antioxidant activity; arrhenius equation; atmospheric pressure; concentration response; drug formulation; drug mechanism; drug potentiation; drug stability; grape; heat stress; isomerism; light; lotion; mathematical computing; oxygen consumption; prescription; shelf life; ultraviolet spectrophotometry